Upaya Pemberdayaan Remaja Untuk Meminimalisir Terjadinya Kesehatan Mental : Literatur Rievew - Lina Eta Safitri; Wahyuliana Wahyuliana; Anissa Julia Ningsih; Alfread Njuka Amah; Evandi Limba Nangi Kewa; Siratjuddin Siratjuddin (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Adolescents are the nation's next golden generation, therefore they need to be the focus of attention to maintain their mental health so that they can produce quality human resources. Mental health is a condition of well-being that an individual is aware of, which includes the abilities to manage normal life stress, to work productively and produce results and to play an active role in the community.(Mental disorders can include symptoms of anxiety, depression which can be described as losing motivation towards something, being irritable, and having thoughts of hurting yourself. Aims to increase knowledge and understanding of teenagers regarding mental health. . This study uses the entire article presented in the form of a literature review regarding "Youth Empowerment Efforts to minimize the occurrence of mental health problems". The results show a significant increase in teenagers' knowledge and understanding regarding Mental Health.